Teorema Ergódico Multiplicativo de Oseledets - Silva, Eberson Ferreira da (2013)
In this paper, we study a version of the Multiplicative Ergodic Theorem of Oseledets for diffeomorphisms of class C1 on a compact Riemannian manifold of finite dimension which ensures the existence of Lyapunov exponents at almost every point with respect to a Borel probability measure invariant by diffeomorphism. In fact, we demonstrate the theorem in a more general version, namely in the context of linear cocycles. The theorem of Oseledets for diffeomorphisms will be established as a special case of this version.